Transforming Natural Resource Wealth into Sustained Growth and Poverty Reduction : A Conceptual Framework for Sub-Saharan African Oil Exporting Countries - Toto Same, Achille (2012)
Oil and mineral revenues raise national savings and hence facilitate investment, capital accumulation, and sustained growth; thus, there are benefits of owning large natural resources. There can be a significant spillover effect from the oil sector to the non-oil sector particularly if governments are committed to bridge the infrastructure gap and promote the non-oil economy and foremost the non-oil tradable sector. Consequently, the capacity for coordinated policy formulation and execution is fundamental as well as sound windfall management mechanisms and institutions. This conceptual framework uses the case of Indonesia and the example of Norway to argue that the resource paradox is avoidable. Abundance should not be a curse, but rather a blessing for Sub-Saharan Africa's oil and mineral exporting countries. The country context and political economy matter a great deal but should not be the main driving forces behind windfall management, to avoid excessive rent-seeking activities, inefficiency, and wasteful spending. The EITI++ implementation can contribute to make a difference, mostly through capacity building, implementation assistance, and coordination support.